Pandemia de covid-19: mudanças e desafios na gestão da atenção hospitalar - MANTESSO, Jhennyfer Barbosa de Oliveira (2023)
INTRODUCTION: In early 2020 covid-19 was classified as a public health emergency of international importance becoming the latest global health crisis. In March of the same year, it was classified as a pandemic, causing changes in health services and work processes. OBJECTIVE: To analyze the challenges in hospital care management during the covid-19 pandemic. METHOD: This study with a qualitative, exploratory approach of the case study type. It was developed in a university hospital in a capital of northeastern Brazil, from March to September 2022. The participants were 22 professionals assigned to management, care or support service in the first and second waves of covid-19. Face-to-face or online interviews were conducted, recorded, and later transcribed, of the individual semi-structured type with the application of a structured questionnaire and interview script. Content analysis was used in the thematic modality. RESULTS: They are presented from two categories: Changes, challenges, and decisions: new emergencies and Conflicts, negotiations and cooperation. The pandemic scenario has required rapid decision-making, often surrounded by uncertainty and insecurity. Structural and organizational changes were identified, related to physical reforms, human resources and related to the work process. Thus, sectors had to be closed and professionals relocated to provide care to patients with covid-19, in most cases, with great initial resistance, requiring the management a posture of imposition, on the one hand, and of negotiation. There was also a barrier in the creation of protocols that were in fact effective, given in part to the denial existing in the federal government that impacted the accreditation of these professionals to include ministerial recommendations in their plans and the lack of effective treatment. Faced with the increase in the demand for care, the departure of some professionals and the licenses due to contamination of the teams, some managers also assumed functions in care. The reports of strengthening cooperation relations between professionals in this scenario of uncertainties were highlighted, facilitating interdisciplinary actions and strategies, and producing a tendency to horizontalization of labor relations. CONCLUSION: The various challenges that arose for management during the pandemic required rapid responses and actions by managers for the organization of services, and the lack of clear national policy guidelines caused anxiety. The daily work, with mistakes and successes, enabled the construction and agreement of strategies to cope with the pandemic, seeking to minimize conflicts, promote integration and ensure the safety of workers, patients and families.